RESPONS ENAM VARIETAS JAMUR TIRAM PUTIH TERHADAP PERTUMBUHAN, HASIL, DAN KUALITAS DIBUDIDAYAKAN MUSIM KEMARAU DAN HUJAN - Etty Sumiati; Deden Fathullah; Rahmat Sutarya (BUANA SAINS, 2014)
Oyster mushroom was a prospective vegetable commodity, potential, and has high economical value. In fact, at the level farmers the average yield is still low in general. The goal of these research activities were to find out oyster mushroom varieties that could be adapted in Bogor-West Java, produced high yield and qualities when cultivated both in the dry and rainy seasons (all the year round). A Randomized Block Design with 4 replications were set up in mushroom houses during the dry and the rainy seasons. Treatments comprised of 6 varieties of oyster mushrooms, viz: varieties No. 1; 30; 37; 38; 46 (origin from IVEGRI`s collection; and no. 85 (origin from Bogor as control variety). Variable to be measured were: vegetative growth of mycelium inoculated on several kinds of growth media, oyster mushrooms yield and yield components, and their qualities as well (viz: storage resistance at ambient/room temperatures, mushrooms taste, and water content). Research results showed that oyster mushroom varieties No. 1, 30, 37, 38, 46, and 85 which were cultivated in dry and rainy season , gave the same high yield, viz: 91,08; 74,36; 78,70; 54,78; 78,91; and 81,40 tons per 1000 m2 of mushroom house area, respectively. Total productions of 6 varieties mentioned above, was higher than that of from cultivation in the rainy season (91,32 vs. 61,76 tons per 1000 m2 of mushroom house area, respectively. The qualities of those six oyster mushroom varieties were the same from cultivation activities all the year round (viz: delicious taste/ ranking: 2 days at room temperature, and water content> 90 %)